The long shadow of German colonialism amnesia, denialism and revisionism - Melber, Henning 1950- (Oxford University Press, 2023)
"From 1884 to 1914, the world's fourth-largest overseas colonial empire was that of the German Kaiserreich. Yet this fact is little known in Germany and the subject remains virtually absent from most school textbooks. While debates are now common in France and Britain over the impact of empire on former colonies and colonizing societies, German imperialism has only more recently become a topic of wider public interest. In 2015, the German government belatedly and half-heartedly conceded that the extermination policies carried out over 1904-8 in the settler colony of German South West Africa (now Namibia) qualify as genocide. But the recent invigoration of debate on Germany's colonial past has been hindered by continued amnesia, denialism and a populist right endorsing colonial revisionism. A recent campaign against postcolonial studies sought to denounce and ostracize any serious engagement with the crimes of the imperial age. Henning Melber presents an overview of German colonial rule and analyses how its legacy has affected and been debated in German society, politics and the media. He also discusses the quotidian experiences of Afro-Germans, the restitution of colonial loot, and how the history of colonialism affects important institutions such as the Humboldt Forum."
Keywords: Geschichte 1884-1914; Kollektives Gedächtnis; Kolonialismus; Völkerrechtliches Verbrechen; Deutschland; Germany / Colonization / History